Physician-therapeutical correlation and molecular aspects of the infection for the HIV in pediatric patients: insearch of the better quality of life - Martins, Juliènne C; Vequi, Danielle B; Silva, Denise G da; Knupp, Rosiangela S; Mello, Paula BM; Godefroy, Philippe; Gardioli, Daniela D; Ferreira, Dennis C; Mirela, Giogo (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the control of the HIV infection in pediatrics patients has reached a larger specter that goes since the boarding of the family in theadhesion to the anti-retroviral treatment until the analysis of the molecular aspects of the infection in this group topromove better quality of life and agreater follow-up. Objective:report the clinical-therapeutical aspects of pediatrics patients infecty by the HIV and describe its psychological correla-tion with the molecular aspects of the infection, nutricionais. In order to emphasize the importance of evaluating these children on the optics of thequality of life. Methods:it was carried through a bibliographical survey that had as base publications of national and international organisms (-Medline and Lilacs), periodic scientific and books technician. Results:the particularitities in the course of the infection for the HIV in pediatricspatients go since the clinical manifestations that differ them from the adults, the necessity of the familiar support in the adhesion to the treatment con-sidered for the doctor until the overcoming of possible adverse effect of the anti-retroviral therapy as the intolerance and the toxicological effects. Onthe other hand ahead of the pathological picture one imposes challenges as to support these children who can develop psychological clutters, to granta diet that contribute in one better action in the treatment, as well as the necessity of if studying the possible mutations that imply in viral resistanceso that the development of new drugs occurs. Conclusion:the clinical-therapeutical course must be the base in the knowledge of the diverse aspectsof the infection for the HIV in pediatrics patients granting to the health professional the basic support in the choice of the ways to supply to one betterquality of life to these patients and a bigger tranquillity during the clinical accompaniment its responsible ones.